Urinary albumin-to-creatinine ratio in decompensated liver cirrhosis among elderly Egyptian patients: a single-center experience - Ahmed Abdelghani; Maha Hosam El-Din Ibrahim; Osama Mohamady Mohamed; Sobhi Eid Rizk; Rabab Mahmoud Ahmed (SpringerOpen, 2021)
Abstract Background Hepatitis C virus and nonalcoholic steatohepatitis (NASH) are the most common causes of liver cirrhosis in Egypt. Increasing aging population is a worldwide issue, and societies are facing various problems, including long-term care for populations with a high prevalence of chronic conditions; hence, comprehensive geriatric assessment is important for determining patients' mental health, functional capacity, and social circumstances. Normally, a small amount of protein (normal urinary albumin-to-creatinine ratio [UACR] < 30 mg/g) excreted in daily urine and excess amounts warrant further examination. The present study aims to evaluate the relationship between UACR and the severity of liver cirrhosis among 47 elderly patients (more than 65 years old) and 47 adult patients (control group) admitted to the hospital as well as the relationship between UACR and geriatric cognitive functions, functional capacity, depression, and nutritional status. Results The present study showed that the cognitive, functional, and nutritional status of patients aged 65 years old or more were significantly affected by the severity of liver disease. The investigators also reported a significant relationship between UACR and Child-Pugh score in the elderly patient group. No significant relationship was found between UACR and the cognitive, functional, mood, or nutritional status of the elderly age group. Conclusion Overall, UACR was correlated to the severity of liver disease among elderly patients compared with adult patients with liver cirrhosis.